A fluorine-doped carbon dot material modified enrichment color film and its application in the detection of three types of perfluorinated compounds

The enriched color-developing film modified by fluorine-doped carbon dot material, combined with UiO-66-F4 and tannin, solves the complex problem of perfluoro compound detection in aqueous environmental samples, and achieves efficient and environmentally friendly perfluoro compound detection.

CN119534444BActive Publication Date: 2025-04-11TIANJIN POLYTECHNIC UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510090320.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-11
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The concentration of perfluoro compounds in the aqueous environment samples is low, the matrix is ​​complex and the interference is high, which makes the sample pretreatment process cumbersome and difficult to detect effectively.

Method used

An enriched color-developing film modified by fluorine-doped carbon dot material was synthesized by a one-pot solvent-thermal method, and combined with UiO-66-F4 and tannin acid to prepare an enriched color-developing film for perfluorine compound detection.

Benefits of technology

It realizes efficient detection of three types of perfluoro compounds in water bodies, simplifies the sample pretreatment process, improves the sensitivity and accuracy of detection, and has the characteristics of environmental protection and degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534444B_ABST
    Figure CN119534444B_ABST
Patent Text Reader

Abstract

The present application provides an enrichment color-developing membrane modified with a fluorine-doped carbon dot material and its application in the detection of three types of perfluorinated compounds. The present application synthesizes the fluorine-doped carbon dot material by a one-pot solvothermal method. 4-diethylamino salicylaldehyde and sodium fluoride are dissolved in deionized water and ultrasonically mixed with phosphoric acid. After the mixture is evenly mixed, it is placed in a polytetrafluoroethylene-lined reactor, and the mixture is heated at 180-220°C for 1-3 hours. After cooling, the resulting solution is centrifuged to remove unreacted products, the upper layer solution is collected, and the sample is placed in a dialysis bag for dialysis for 24-48 hours. The sample is freeze-dried to prepare the fluorine-doped carbon dot material. The fluorine-doped carbon dot material is used as a color developer to achieve the purpose of detecting perfluorinated compounds, and is combined with UiO-66-F4 to prepare an enrichment color-developing membrane, which is convenient for detection and achieves the effect of in-situ monitoring of three types of perfluorinated compounds in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of detection technology, and in particular to an enriched color-developing membrane modified with a fluorine-doped carbon dot material and its application in the detection of three types of perfluorinated compounds. Background Art

[0002] Perfluorinated compounds are a class of organic compounds containing the element fluorine, in which all hydrogen atoms are replaced by fluorine atoms. Due to the strong electronegativity of fluorine atoms, perfluorinated compounds are extremely stable and chemically inert, which makes them difficult to degrade in the environment. Common perfluorinated compounds PFOS and PFOA have been widely used in fields such as kitchen utensils, hydrophobic coatings, and food packaging materials. However, their potential toxicity and carcinogenicity, coupled with their persistence, bioaccumulation, and tendency to migrate over long distances in the environment, long-term exposure to or accumulation of these compounds may pose potential risks to human health and the environment, including endocrine disruption, liver damage, and ecosystem destruction. Therefore, it is very necessary to establish effective analytical methods to detect perfluorinated compounds in the environment. There are many types of perfluorinated compounds (PFCs), which can be divided into multiple categories according to their structure and function. Globally, PFCs are widely used in industrial production and consumer products, and there are significant differences in the proportion of different types of PFCs in environmental distribution and use. Among them, perfluorocarboxylates (such as PFOA), perfluorosulfonic acids (such as PFOS) and perfluoropolyethers (such as PPVE) account for the highest proportion, so these three types of perfluoro compounds have become the focus of research.

[0003] Carbon dots (CDs) are a class of carbon-based materials with nanoscale dimensions, usually with diameters ranging from a few nanometers to tens of nanometers. They are composed of carbon atoms and usually contain functional groups of oxygen, nitrogen or other elements, which give them excellent optical properties, such as strong fluorescence emission. Due to their excellent biocompatibility, low toxicity and good photostability, carbon dots have a wide range of applications in bioimaging, sensors, catalysis and drug delivery.

[0004] The enrichment colorimetric membrane is a material that combines membrane separation technology and colorimetric reaction, and is used to detect and concentrate specific target substances. Through the unique pore structure and surface functionalization of the membrane, the target substance is enriched on the membrane surface, and reacts with the colorimetric reagent embedded in the membrane to produce a significant color change. This colorimetric reaction not only helps to visualize the concentration of the target substance, but also improves the sensitivity and accuracy of the detection. Since perfluorinated compounds in water environment samples have the characteristics of low concentration, complex matrix, and many interferences, the sample pretreatment process is usually cumbersome. Therefore, it is of great significance to develop a degradable, environmentally friendly enrichment colorimetric membrane that can effectively avoid interference from other factors for the detection of perfluorooctanoic acid, perfluorooctane sulfonic acid and perfluoropropyl vinyl ether in the water environment. Summary of the invention

[0005] In order to solve the above technical problems, this application is proposed. The embodiments of this application provide an enrichment colorimetric membrane modified with fluorine-doped carbon dot materials and its application in the detection of three types of perfluorinated compounds, which solves the technical problem that the sample pretreatment process is usually cumbersome in the prior art due to the low concentration, complex matrix, and many interferences of perfluorinated compounds in water environment samples.

[0006] According to one aspect of the present application, a method for preparing fluorine-doped carbon dot materials is provided, wherein the fluorine-doped carbon dot materials are synthesized by a one-pot solvothermal method: 4-diethylaminosalicylaldehyde and sodium fluoride are dissolved in water and ultrasonically mixed with phosphoric acid. After the mixture is evenly mixed, the mixture is placed in a reactor for heating reaction. After cooling, the unreacted products are removed, the upper layer solution is collected and dialyzed, and the sample is freeze-dried to obtain the fluorine-doped carbon dot material (CDs-F).

[0007] In one embodiment, the volume ratio of 4-diethylamino salicylaldehyde, sodium fluoride and phosphoric acid is (2-2.5): (1-2): (0.05-0.15).

[0008] In one embodiment, the temperature of the heating reaction is 180-220°C, preferably, the temperature of the heating reaction is 200°C; and / or, the reaction time is 1-3h, preferably, the reaction time is 2h; and / or, dialysis is performed in a dialysis bag, and the dialysis time is 24-48h.

[0009] According to the second aspect of the present application, the present application provides a method for preparing a fluorine-doped carbon dot material-modified enriched color-developing film, comprising: preparing a base film: first modifying PVDF to obtain αAA-PVDF, then dissolving αAA-PVDF and polyvinyl pyrrolidone in N,N-dimethylformamide, stirring at 60-70°C for 10-12h, standing for 10-18h, then pouring it on a film scraping machine to scrape the film to obtain the enriched color-developing film, and soaking the enriched color-developing film in deionized water for standby use; preparing a tannic acid solution; Preparation: dissolving tannic acid powder in phosphate buffer to obtain a tannic acid solution; dispersing the above-mentioned fluorine-doped carbon dot material and UiO-66-F4 in deionized water and ultrasonically obtaining a dispersion of UiO-66-F4 and fluorine-doped carbon dot material; cutting the prepared base film and immersing it in the tannic acid solution and letting it stand for 20-60 minutes, and then immersing it in the dispersion of UiO-66-F4 and fluorine-doped carbon dot material and letting it stand for 20-60 minutes to obtain an enriched color-developing film modified with UiO-66-F4 and fluorine-doped carbon dot material.

[0010] In one embodiment, the modification of PVDF comprises the following steps: step (1), dispersing PVDF powder in a KOH solution at 50-60°C, adding ethanol and continuing to stir for 20-60 minutes, then collecting by suction to obtain α-PVDF powder, washing the α-PVDF powder with deionized water until it is neutral, and drying for standby use; step (2), adding the α-PVDF powder obtained in step (1) into DMF and filling with nitrogen to drive out oxygen for 20-40 minutes, stirring and dissolving, adding acrylic acid and 2,2-azobisisobutyronitrile, reacting at a constant temperature of 55-70°C with stirring for 8-12 hours, adding methanol to precipitate it, and washing the αAA-PVDF powder with deionized water, and drying for standby use.

[0011] In one embodiment, in the preparation of the tannic acid solution, tannic acid powder is dissolved in a phosphate buffer with a pH value of 8 to obtain a tannic acid solution, and the concentration of tannic acid in the tannic acid solution is 2-4 g / L.

[0012] In one embodiment, the concentration of KOH in the KOH solution is 56 g / L.

[0013] In one embodiment, the concentration of the UiO-66-F4 and fluorine-doped carbon dot material in the UiO-66-F4 and fluorine-doped carbon dot material dispersion is 1 g / L.

[0014] According to the third aspect of the present application, the present application provides a detection box, comprising an enrichment color-developing film, a box body, a light source, a collection window, a camera device bracket, a shooting device, a sample stage, a light source switch and a microfluidic chip, wherein the enrichment color-developing film is prepared by the preparation method described above; the collection window is opened at the top of the box body, the sample stage is arranged on the bottom inner wall of the box body, the collection window is arranged parallel to the sample stage, and the microfluidic chip is placed on the sample stage; the light source is arranged at the top of the box body and symmetrically arranged on both sides of the collection window; the camera device bracket is arranged on one side of the collection window, and the shooting device is placed on the camera device bracket; the microfluidic chip comprises an upper chip, a lower chip and a gasket; a sample inlet, a microchannel, an enrichment color-developing film and a detection area are arranged on the upper chip, the sample inlet is arranged at the center of the upper chip, the detection area is connected to the sample inlet through the microchannel, the enrichment color-developing film is placed in the detection area, the gasket is arranged at the bottom of the enrichment color-developing film, and the upper chip and the lower chip are connected together through the gasket.

[0015] According to the fourth aspect of the present application, the present application provides the use of the enriched color developing membrane modified with the above-mentioned fluorine-doped novel carbon dot material or the above-mentioned detection kit in the detection of three types of perfluorinated compounds.

[0016] The present application provides an enriched color-developing membrane of a fluorine-doped carbon dot material and its application in the detection of three types of perfluorinated compounds. The present application adopts a one-pot solvent thermal method to synthesize the fluorine-doped carbon dot material: 4-diethylamino salicylaldehyde and sodium fluoride are dissolved in water and then ultrasonically mixed with phosphoric acid. After the mixture is evenly mixed, it is placed in a reactor for heating reaction, and the unreacted products are removed after cooling. The upper solution is collected and dialyzed, and the sample is freeze-dried to obtain the fluorine-doped carbon dot material. The prepared PVDF enriched color-developing membrane is cut and first immersed in a tannic acid solution and allowed to stand for 20-60 minutes, and then immersed in UiO-66-F4 and a fluorine-doped carbon dot material dispersion and allowed to stand for 20-60 minutes. After being treated as a color developer to achieve the purpose of detecting perfluorinated compounds, the enriched color-developing membrane is prepared in combination with UiO-66-F4, which is convenient for detection and achieves the effect of in-situ monitoring of the three types of perfluorinated compounds in water. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] By describing the embodiments of the present application in more detail in conjunction with the accompanying drawings, the above and other purposes, features and advantages of the present application will become more apparent. The accompanying drawings are used to provide a further understanding of the embodiments of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the present application and do not constitute a limitation of the present application. In the accompanying drawings, the same reference numerals generally represent the same components or steps.

[0018] Figure 1 is a fluorescence spectrum curve and a linear standard curve of the fluorine-doped carbon dot material to perfluorooctanoic acid provided in Experimental Example 1 of the present application, Figure 1 (a) is the fluorescence spectrum curve of fluorine-doped carbon dot material to perfluorooctanoic acid. Figure 1 (b) is the linear standard curve of fluorine-doped carbon dots material to perfluorooctanoic acid;

[0019] Figure 2 is a fluorescence spectrum curve and a linear standard curve of the fluorine-doped carbon dot material to perfluorooctane sulfonic acid provided in Experimental Example 1 of the present application, Figure 2 (a) is the fluorescence spectrum curve of fluorine-doped carbon dot material to perfluorooctane sulfonic acid. Figure 2 (b) is the linear standard curve of fluorine-doped carbon dots material to perfluorooctane sulfonic acid;

[0020] Figure 3 is the fluorescence spectrum curve and linear standard curve of the fluorine-doped carbon dot material to perfluoropropyl vinyl ether provided in Experimental Example 1 of the present application, Figure 3 (a) is the fluorescence spectrum curve of fluorine-doped carbon dot material to perfluoropropyl vinyl ether. Figure 3 (b) is the linear standard curve of fluorine-doped carbon dots material to perfluoropropyl vinyl ether;

[0021] Figure 4This is a characterization diagram of an enriched color-developing membrane provided by an exemplary embodiment of the present application: Figure 4 (a) is a scanning electron microscope image of the enriched color-developing membrane surface. Figure 4 (b) is a scanning electron microscope image of the cross section of the enriched color-developing membrane. Figure 4 (c) is the infrared spectrum of the enriched color film. Figure 4 (d) is the XRD spectrum of the enriched color film;

[0022] Figure 5 It is a schematic diagram of the structure of a membrane-based microfluidic coupling chip and a detection box used in combination therewith provided by an exemplary embodiment of the present application;

[0023] Figure 6 is a schematic diagram of the structure of a membrane-based microfluidic coupling chip provided by an exemplary embodiment of the present application;

[0024] Figure 7 The central area diagram and linear standard curve diagram of the fluorescence image extraction of perfluorooctanoic acid by the enriched color developing membrane provided in Experimental Example 2 of this application are shown in FIG. Figure 7 (a) is the central area of ​​the fluorescence image extracted from the enriched color film for perfluorooctanoic acid. Figure 7 (b) is the linear standard curve of the enriched colorimetric membrane for perfluorooctanoic acid;

[0025] Figure 8 The central area diagram and linear standard curve diagram of the fluorescence image extraction of perfluorooctane sulfonic acid by the enriched color developing membrane provided in Experimental Example 3 of the present application are shown in FIG. Figure 8 (a) is the central area of ​​the fluorescence image extracted from the enriched color film for perfluorooctane sulfonic acid. Figure 8 (b) is the linear standard curve of the enriched colorimetric membrane for perfluorooctane sulfonic acid;

[0026] Fig. 9 The central area diagram and linear standard curve diagram of the fluorescence image extraction of perfluoropropyl vinyl ether by the enriched color developing membrane provided in Experimental Example 4 of the present application are shown in FIG. Fig. 9 (a) is the central area of ​​the fluorescence image extracted from the enriched color film for perfluoropropyl vinyl ether. Fig. 9 (b) is the linear standard curve of the enriched color film for perfluoropropyl vinyl ether;

[0027] Fig.10 It is the ultraviolet spectra of PFOS, CDs-F and PFOS / CDs-F provided in Experimental Example 5 of the present application;

[0028] Fig.11 It is the excitation spectrum and emission spectrum of CDs-F and the ultraviolet spectrum of PFOS provided in Experimental Example 5 of the present application;

[0029] Fig.12This is the fluorescence lifetime diagram of CDs-F before and after adding PFOS provided in Experimental Example 5 of the present application.

[0030] Description of reference numerals:

[0031] 1. Box body; 2. Light source; 3. Collection window; 4. Camera device bracket; 5. Shooting device; 6. Light source switch; 7. Sample stage; 8. Microfluidic chip; 9. Upper chip; 10. Sample inlet; 11. Microchannel; 12. Detection area; 13. Color film; 14. Gasket; 15. Lower chip. DETAILED DESCRIPTION

[0032] Below, the exemplary embodiments according to the present application will be described in detail with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application, and it should be understood that the present application is not limited to the exemplary embodiments described here.

[0033] Example 1

[0034] Preparation method of fluorine-doped carbon dot materials:

[0035] The fluorine-doped carbon dot material was synthesized by a one-pot solvothermal method. The specific steps were as follows: 4-diethylaminosalicylaldehyde and sodium fluoride were dissolved in deionized water and then ultrasonically mixed with phosphoric acid. The volume ratio of 4-diethylaminosalicylaldehyde, sodium fluoride and phosphoric acid was 2:1:0.1. After being evenly mixed, they were placed in a polytetrafluoroethylene-lined reactor and reacted at 200°C for 2h. After cooling, the unreacted products were removed by centrifugation, the upper solution was collected, placed in a dialysis bag for 48h, and then the sample was freeze-dried for 12h to prepare the fluorine-doped carbon dot material.

[0036] Polytetrafluoroethylene (PTFE) lined autoclaves are mainly used in chemical laboratories and industrial production to carry out reactions that require resistance to high temperature, high pressure and highly corrosive chemicals. Polytetrafluoroethylene has excellent chemical stability and non-stickiness, which makes it an ideal choice for lining materials. This type of autoclave can usually withstand extreme temperature and pressure conditions without chemical decomposition or physical form changes. The pressure range of laboratory-grade autoclaves is generally 100 to 500 atmospheres (approximately 1500 to 7500 psi).

[0037] Example 2

[0038] The method for preparing the color developing film of fluorine-doped carbon dot material comprises the following steps:

[0039] Step (1): First, 10 g of PVDF powder was uniformly added to a KOH solution in a 50°C constant temperature water bath to disperse the powder well, ethanol was added and stirring was continued, and α-PVDF powder was collected by suction after 30 minutes, and washed with deionized water until it was neutral, and dried for use. The concentration of KOH in the KOH solution was 56 g / L.

[0040] Step (2): Add the treated α-PVDF powder into DMF and aerate with nitrogen for 30 min. Then, add acrylic acid and 2,2-azobisisobutyronitrile after stirring and dissolving, and react at 60°C for 10 h. Add methanol to convert the product into a gel precipitate, and wash with deionized water to obtain αAA-PVDF, which is then dried for later use.

[0041] Step (3): Weigh 2 g of αAA-PVDF obtained in step (2) and 0.2 g of polyvinyl pyrrolidone, dissolve them in 20 ml of N,N-dimethylformamide as a casting solution, stir at 60°C for 12 h, let stand for 12 h, pour the casting solution onto a scraper, scrape the film with a scraper to obtain a homogeneous base film, and soak the base film in deionized water, changing the water every 12 hours.

[0042] The tannic acid powder is dissolved in a phosphate buffer with a pH value of 8 to obtain a tannic acid solution, wherein the concentration of the tannic acid in the tannic acid solution is 3 g / L.

[0043] Weigh UiO-66-F4 and fluorine-doped carbon dot materials, dissolve them in deionized water and ultrasonicate to obtain a dispersion of UiO-66-F4 and fluorine-doped carbon dot materials. The concentration of UiO-66-F4 and fluorine-doped carbon dot materials in the dispersion of UiO-66-F4 and fluorine-doped carbon dot materials is 1 g / L.

[0044] The base film prepared in step (3) is cut into a suitable size, and immersed in tannic acid solution, UiO-66-F4 and fluorine-doped carbon dot material dispersion in turn, and allowed to stand at room temperature for 30 minutes to achieve modification and assembly of each component on the surface of the base film to obtain an enriched color film.

[0045] Figure 4 This is a characterization diagram of the enriched color-developing membrane provided in Example 2 of the present application: Figure 4 (a) is a scanning electron microscope image of the enriched color-developing membrane surface. Figure 4 (b) is a scanning electron microscope image of the cross section of the enriched color-developed membrane. Figure 4 (a) and Figure 4 As shown in (b), it can be clearly seen that fluorine-doped carbon dot materials are deposited on the surface of the base film, and the UiO-66-F4 nanoparticles on the surface of the base film are well dispersed, which indicates that with the assistance of tannic acid, UiO-66-F4 and fluorine-doped carbon dot materials are uniformly assembled on the surface of the base film to obtain an enriched color film; Figure 4(c) is the infrared spectrum of the enriched color film. Figure 4 As shown in (c), the enriched color film is at 1000 cm -1 The absorption peaks on the left and right sides are enhanced, which indicates that UiO-66-F4 has grown on the membrane, and the enriched color film is at 1200cm -1 There are signal peaks near 1000 cm-1, which indicates that there is Zr-OH in the enriched chromogenic film. The enriched chromogenic film-PFOS (enriched chromogenic film after adsorption of perfluorinated compound samples) has a peak at 1000 cm-1. -1 There is an obvious absorption peak nearby, which is the stretching vibration peak of the CF bond; Figure 4 (d) is the XRD spectrum of the enriched color film. Figure 4 As shown in (d), the peak of the enriched color film is wider, which indicates that the surface of the enriched color film has a good crystal structure and high crystallinity. During the preparation process, although the peak intensity of the enriched color film decreased and the crystallinity of the material decreased, the position of the peak remained basically unchanged, indicating that the basic crystal structure of UiO-66-F4 still exists, but its grain size or dispersion state has changed. Figure 4 It can be seen that UiO-66-F4 and fluorine-doped carbon dot materials are uniformly assembled on the surface of the base film under the action of tannic acid.

[0046] Example 3

[0047] Figure 5 A membrane-based microfluidic coupling chip and a detection box used in combination are provided in an exemplary embodiment of the present application. Figure 6 is a schematic diagram of the structure of a membrane-based microfluidic coupling chip provided by an exemplary embodiment of the present application; Figure 5 as well as Figure 6 As shown, the detection box can be used to detect perfluorinated compounds in water. The detection box includes a color developing film 13, a box body 1, a light source 2, a collection window 3, a camera device bracket 4, a shooting device 5, a light source switch 6, a sample stage 7 and a microfluidic chip 8.

[0048] The color developing film 13 is prepared by the above-mentioned preparation method; the collection window 3 is opened at the top of the box body 1, the sample stage 7 is arranged on the bottom inner wall of the box body 1, the collection window 3 is arranged in parallel with the sample stage 7, and the microfluidic chip 8 is placed on the sample stage 7; the camera device bracket 4 is arranged on one side of the collection window 3, and the shooting device 5 is placed on the camera device bracket 4; the shooting device 5 is used to shoot the color developing film 13 on the sample stage 7 through the collection window 3, the light source 2 is arranged on the top of the box body 1, and is symmetrically arranged on both sides of the collection window 3, the light source 2 is an ultraviolet light source, and the ultraviolet light source is used to irradiate the color developing film 13;

[0049] The microfluidic chip 8 includes an upper chip 9, a lower chip 15 and a gasket 14; a sample inlet 10, a microchannel 11, a color developing film 13 and a detection area 12 are arranged on the upper chip 9, the sample inlet 10 is arranged at the center of the upper chip 9, the detection area 12 is connected to the sample inlet 10 through the microchannel 11, the color developing film 13 is placed in the detection area 12, and the gasket 14 is arranged at the bottom of the color developing film 13, and the upper chip 9 and the lower chip 15 are connected together through the gasket 14.

[0050] Specifically, the sample is injected into the sample inlet 10, and the sample enters the detection area 12 through the microchannel 11, and is discharged after passing through the color-developing membrane 13. After a certain volume of sample is injected, the microfluidic chip 8 is placed on the sample stage 7, and the shooting device 5 (which can be a mobile phone) is placed on the camera bracket 4. The light source 2 is turned on by the light source switch 6 to collect the image. After collecting the image, the RGB value of the color-developing area of ​​the obtained image is extracted, and the standard curve is obtained by analyzing the relationship between the RGB value and the concentration. The standard solution of perfluorinated compounds of different concentrations is adsorbed on the enriched color-developing membrane through the microfluidic chip, and as the concentration increases, the color of the membrane gradually changes, producing an obvious color response. Substituting the RGB value of the sample to be tested into the standard curve, the concentration of the perfluorinated compound in the sample to be tested can be obtained.

[0051] Experimental Example 1

[0052] The prepared fluorine-doped carbon dot material (CDs-F) was subjected to fluorescence spectral curves and linear standard curves with perfluorooctanoic acid, perfluorooctane sulfonic acid, and perfluoropropyl vinyl ether, respectively.

[0053] Figure 1 is a fluorescence spectrum curve diagram and a linear standard curve diagram of the fluorine-doped carbon dot material to perfluorooctanoic acid provided in Example 1 of the present application, Figure 1 (a) is the fluorescence spectrum curve of fluorine-doped carbon dot material to perfluorooctanoic acid. Figure 1 (b) is the linear standard curve of fluorine-doped carbon dots material to perfluorooctanoic acid. Figure 2 is a fluorescence spectrum curve and a linear standard curve of the fluorine-doped carbon dot material to perfluorooctane sulfonic acid provided in Example 1 of the present application, Figure 2 (a) is the fluorescence spectrum curve of fluorine-doped carbon dot material to perfluorooctane sulfonic acid. Figure 2 (b) is the linear standard curve of fluorine-doped carbon dots material to perfluorooctane sulfonic acid. Figure 3 is a fluorescence spectrum curve and a linear standard curve of the fluorine-doped carbon dot material to perfluoropropyl vinyl ether provided in Example 1 of the present application, Figure 3 (a) is the fluorescence spectrum curve of fluorine-doped carbon dot material to perfluoropropyl vinyl ether. Figure 3(b) is the linear standard curve of fluorine-doped carbon dots material to perfluoropropyl vinyl ether. Figure 1-3 As shown, after the preparation of the fluorine-doped carbon dot material is completed, in order to test its performance, the fluorescence quenching of the fluorine-doped carbon dot material by perfluorooctanoic acid, perfluorooctane sulfonic acid and perfluoropropyl vinyl ether at concentrations of 1, 2, 4, 8, and 10 μM is tested by a fluorescence spectrometer. The fluorescence values ​​generated by the tests of different concentrations of perfluorooctanoic acid, perfluorooctane sulfonic acid and perfluoropropyl vinyl ether are linearly fitted, and relatively considerable fitting values ​​are obtained, which indicates that the fluorine-doped carbon dot material can be used to detect the above-mentioned perfluorinated compounds.

[0054] Experimental Example 2

[0055] The perfluorooctanoic acid standard solutions with concentrations of 1, 2, 4, 8, and 10 μM were adsorbed on the enriched color-developing membrane through the microfluidic chip. As the concentration increased, the color of the enriched color-developing membrane gradually changed, producing an obvious color response. The enriched color-developing membrane was photographed in sequence by a mobile phone to collect colorimetric images, and then the obtained images were imported into the software to extract the RGB value of the color-developing area, analyze the linear relationship between the B value and the perfluorooctanoic acid concentration, and obtain the standard curve. Figure 7 It is the central area diagram and linear standard curve diagram of the fluorescence image extraction of perfluorooctanoic acid by the enriched color developing membrane provided in Experimental Example 2 of this application, Figure 7 (a) is the central area of ​​the fluorescence image extracted from the enriched color film for perfluorooctanoic acid. Figure 7 (b) is the linear standard curve of the enrichment colorimetric membrane for perfluorooctanoic acid. Figure 7 Substituting the B value of the sample to be tested into the standard curve, the concentration of perfluorooctanoic acid in the sample to be tested can be obtained.

[0056] Experimental Example 3

[0057] 1, 3, 6, 8, 10 μM PFOS standard solutions were adsorbed on the enriched colorimetric membrane through a microfluidic chip. As the concentration increased, the color of the enriched colorimetric membrane gradually changed, producing an obvious color response. The enriched colorimetric membrane was photographed in sequence with a mobile phone to collect colorimetric images. The obtained images were then imported into the software to extract the G value of the colorimetric area, analyze the linear relationship between the RGB value and the PFOS concentration, and obtain the standard curve. Figure 8 It is the central area diagram and linear standard curve diagram of the fluorescence image extraction of perfluorooctane sulfonic acid by the enriched color developing membrane provided in Experimental Example 3 of the present application, Figure 8 (a) is the central area of ​​the fluorescence image extracted from the enriched color film for perfluorooctane sulfonic acid. Figure 8 (b) is the linear standard curve of the enriched colorimetric membrane for perfluorooctane sulfonic acid. Figure 8Substituting the G value of the sample to be tested into the standard curve, the concentration of PFOS in the sample to be tested can be obtained.

[0058] Experimental Example 4

[0059] 1, 4, 6, 8, 10 μM perfluoropropyl vinyl ether standard solutions were adsorbed on the enriched color-developing membrane through a microfluidic chip. As the concentration increased, the color of the membrane gradually changed, producing an obvious color response. The enriched color-developing membrane was photographed in sequence with a mobile phone to collect colorimetric images. The obtained images were then imported into the software to extract the RGB value of the color-developing area, and the linear relationship between the B value and the perfluorooctanoic acid concentration was analyzed to obtain a standard curve. Fig. 9 It is a central area diagram and a linear standard curve diagram of the fluorescence image extraction of perfluoropropyl vinyl ether by the enriched color developing membrane provided in Experimental Example 4 of the present application, Fig. 9 (a) is the central area of ​​the fluorescence image extracted from the enriched color film for perfluoropropyl vinyl ether. Fig. 9 (b) is the linear standard curve of the enriched color film for perfluoropropyl vinyl ether, as shown in Fig. 9 Substituting the B value of the sample to be tested into the standard curve, the concentration of perfluoropropyl vinyl ether in the sample to be tested can be obtained.

[0060] Experimental Example 5

[0061] In order to study the fluorescence quenching mechanism of PFOS (perfluorooctane sulfonic acid) on CDs-F (fluorine-doped carbon dot material), UV spectra of PFOS, CDs-F and PFOS / CDs-F (fluorine-doped carbon dot material after adding PFOS) were tested respectively. Fig.10 is the UV spectra of PFOS, CDs-F and PFOS / CDs-F provided in Experimental Example 5 of the present application; Fig.10 As shown, no new UV absorption peak appeared after adding PFOS to CDs-F, and there was no non-radiative ground state complex between CDs and PFOS, thus excluding the possibility of static quenching.

[0062] Fig.11 The excitation spectrum and emission spectrum of CDs-F and the ultraviolet absorption spectrum of PFOS provided in Experimental Example 5 of this application are shown in FIG. Fig.11 As shown, the excitation spectrum of CDs-F partially overlaps with the UV absorption spectrum of PFOS in the range of 215-246 nm, which indicates that the quenching mechanism may be an internal filter effect or fluorescence resonance energy transfer.

[0063] Fig.12 The fluorescence lifetime diagram of CDs-F before and after adding PFOS provided in Experimental Example 5 of the present application is as follows: Fig.12As shown in the figure, the average fluorescence lifetimes of CDs-F in the presence and absence of PFOS are 137.22 ps and 137.83 ps, respectively, which indicates that the introduction of PFOS does not change the fluorescence lifetime of CDs-F, thereby excluding the possibility of fluorescence resonance energy transfer, indicating that the fluorescence quenching of CDs-F by PFOS is caused by the internal filtering effect rather than other potential mechanisms.

[0064] Combined with the above FT-IR analysis, due to the ion exchange between fluoride ions and hydroxyl ions, the adsorption of PFOS can be promoted by molecular diffusion, electrostatic interaction, hydrophobic interaction, hydrogen bonding, and FF bonding. First, the target compound can diffuse into the pores of the enriched color-developing membrane through close contact with UiO-66-F4. Second, the sulfonate or carboxylate groups of PFOS can coordinate with the unsaturated Zr of UiO-66-F4. 4+ The electrostatic adsorption that may occur between sites may be a key factor for effective extraction. Third, PFOS can be adsorbed through hydrophobic interactions between hydrophobic parts, coordination of PFOS with zirconium clusters, or fluorophilic interactions. Fourth, there may be hydrogen bonding interactions between Zr-coordinated water ligands and PFOS. In addition, the F of PFOS forms FF stacking with the F of UiO-66-F4 separation membrane, which also has an adsorption effect on PFOS.

[0065] It can be seen that the present application uses a microfluidic chip to adsorb perfluorinated compound standard solutions of different concentrations on an enriched color-developing membrane, and as the concentration increases, the color of the enriched color-developing membrane gradually changes, producing an obvious color response. The enriched color-developing membrane is photographed in sequence by a mobile phone, and a colorimetric image is collected. The obtained image is then imported into the software to extract the RGB value of the color-developing area, and the linear relationship between the RGB value and the concentration of perfluorinated compounds is analyzed to obtain a standard curve. The RGB value of the sample to be tested is substituted into the standard curve to obtain the concentration of perfluorinated compounds in the sample to be tested. By using a smart phone to collect colorimetric images, the image color blocks are extracted and analyzed, and the detection range is wide. As a color developer, the purpose of detecting perfluorinated compounds is achieved, and the enriched color-developing membrane is prepared in combination with UiO-66-F4, which is convenient for detection and achieves the effect of in-situ monitoring of perfluorinated compounds in water bodies.

Claims

1. A method for preparing a fluorine-doped carbon dot material-modified enriched color-developing film, characterized in that: include: Preparation of base film: first modify PVDF to obtain αAA-PVDF, then dissolve αAA-PVDF and polyvinyl pyrrolidone in N,N-dimethylformamide, stir at 60-70°C for 10-12h, let stand for 10-18h, pour on a film scraping machine to scrape the base film, and soak the base film in deionized water for standby use; Preparation of tannic acid solution: dissolving tannic acid powder in phosphate buffer to obtain tannic acid solution; Dispersing the fluorine-doped carbon dot material and UiO-66-F4 in deionized water and ultrasonicating to obtain a dispersion of UiO-66-F4 and fluorine-doped carbon dot material; Cut the prepared base film, immerse it in a tannic acid solution and let it stand for 20-60 minutes, and then immerse it in a UiO-66-F4 and fluorine-doped carbon dot material dispersion and let it stand for 20-60 minutes to obtain the enriched color film; The modification of the PVDF comprises the following steps: Step (1), dispersing PVDF powder in a 50-60°C KOH solution, adding ethanol and continuing to stir for 20-60 minutes, then collecting by suction to obtain α-PVDF powder, washing the α-PVDF powder with deionized water until it is neutral, and drying for standby use; Step (2), adding the α-PVDF powder obtained in step (1) into DMF and aerating nitrogen to drive out oxygen for 20-40 minutes, adding acrylic acid and 2,2-azobisisobutyronitrile after stirring to dissolve, reacting at a constant temperature of 55-70° C. for 8-12 hours under stirring, adding methanol to precipitate, and washing the αAA-PVDF powder with deionized water, and drying for standby use.

2. The preparation method according to claim 1, characterized in that: Fluorine-doped carbon dot materials were synthesized by a one-pot solvothermal method: 4-diethylaminosalicylaldehyde and sodium fluoride were dissolved in water and ultrasonically mixed with phosphoric acid. After the mixture was evenly mixed, it was placed in a reactor for heating reaction. After cooling, the unreacted products were removed, the upper solution was collected and dialyzed, and the sample was freeze-dried to obtain the fluorine-doped carbon dot material.

3. The preparation method according to claim 2, characterized in that: The volume ratio of the 4-diethylamino salicylaldehyde, sodium fluoride and phosphoric acid is (2-2.5): (1-2): (0.05-0.15).

4. The preparation method according to claim 2, characterized in that: The temperature of the heating reaction is 180-220° C., and / or the reaction time is 1-3 hours, and / or the dialysis is performed in a dialysis bag for 24-48 hours.

5. The preparation method according to claim 1, characterized in that: In the preparation of the tannic acid solution, tannic acid powder is dissolved in a phosphate buffer with a pH value of 8 to obtain a tannic acid solution, and the concentration of the tannic acid in the tannic acid solution is 2-4 g / L.

6. The preparation method according to claim 1, characterized in that: The concentration of KOH in the KOH solution is 56 g / L.

7. The preparation method according to claim 1, characterized in that: The concentration of the UiO-66-F4 and fluorine-doped carbon dot material in the UiO-66-F4 and fluorine-doped carbon dot material dispersion is 1 g / L.

8. A detection kit, characterized in that: It comprises an enriched color-developing film, a box body, a light source, a collection window, a camera device bracket, a shooting device, a sample stage and a microfluidic chip, wherein the enriched color-developing film is prepared by the preparation method according to any one of claims 1 to 7; The collection window is opened on the top of the box body, the sample stage is arranged on the bottom inner wall of the box body, the collection window is arranged parallel to the sample stage, and the microfluidic chip is placed on the sample stage; The light source is arranged on the top of the box body and symmetrically arranged on both sides of the collection window; The camera support is arranged at one side of the acquisition window, and the shooting device is placed on the camera support; The microfluidic chip includes an upper chip, a lower chip and a gasket; a sample inlet, a microchannel, an enrichment colorimetric film and a detection area are arranged on the upper chip, the sample inlet is arranged at the center of the upper chip, the detection area is connected to the sample inlet through the microchannel, the enrichment colorimetric film is placed in the detection area, the gasket is arranged at the bottom of the enrichment colorimetric film, and the upper chip and the lower chip are connected together through the gasket.

9. Use of the enriched color developing membrane modified with fluorine-doped carbon dots prepared by the preparation method according to any one of claims 1 to 7 or the detection kit according to claim 8 in the detection of three types of perfluorinated compounds, characterized in that: The perfluorinated compounds are perfluorooctanoic acid, perfluorooctane sulfonic acid and perfluoropropyl vinyl ether.

Citation Information

Patent Citations

  • Preparation method of doped fluorine ion carbon dot and application thereof

    CN107529514A

  • Carbon quantum dot / manganese dioxide composite fluorescent probe, preparation method thereof and application of carbon quantum dot / manganese dioxide composite fluorescent probe in determination of uric acid

    CN118792043A